PERAN PT PERMODALAN NASIONAL MADANI (PNM) MEKAR DALAM MENDORONG INKLUSI KEUANGAN UMKM MELALUI PEMBIAYAAN SYARIAH - Saifuddin; Suwaibatul Aslamiyah (Penerbit Lafadz Jaya, 2025)
Financial inclusion is an important aspect in the development of the community economy, especially in remote areas with limited financial access. PT PNM Mekar through its sharia financing program acts as a facilitator of capital access in accordance with Islamic principles and provides business assistance to MSMEs in Pesisir Besuki Village. This study aims to examine the role of PT Permodalan Nasional Madani (PNM) Mekar in encouraging financial inclusion for MSMEs through sharia-based financing in Pesisir Besuki Village. This study uses a qualitative approach to gain a deeper understanding of the impact of the program. The data collection techniques include in-depth interviews with MSMEs, direct observations in the field, and documentation of assistance activities carried out by PNM Mekaar. The results of the study show that before receiving financing, most MSME actors experience limited access to formal financial institutions, minimal knowledge about sharia financial management, and obstacles in business development due to limited capital. Business actors tend to rely on very limited personal capital. However, after becoming customers of PT PNM Mekar and receiving sharia financing through the murabahah contract, MSME actors experienced increased access to capital, were able to develop their businesses more optimally and showed an increase in understanding of financial management and business records. The implemented sharia financing program was able to provide a real contribution to improving people's standard of living. This is reflected in the increased business capacity and understanding of local communities regarding sharia financial literacy.